2019
DOI: 10.1002/slct.201903230
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study on the Photochemistry of 2,4,4‐Trimethyl‐1‐pyrroline 1‐Oxide and Investigation on the Reaction Paths of Its Photoproduct Oxaziridine

Abstract: This computational study reveals the reaction pathways of the experimentally reported photo‐conversion of 2,4,4‐trimethyl‐1‐pyrroline 1‐oxide to oxaziridine and the subsequent reactions (thermal and photochemical) of this photo‐product. The latter involve the oxaziridine to N‐acetyl azetidine, pyrrolidone and pyrroline formation paths. The photo‐excitation of the cyclic nitrone gives weakly allowed S0‐S1 and strongly allowed S0‐S2 transitions with transition moment values of 0.12 D and 3.16 D, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In the recent years, our group has been actively involved in the investigations on the photochemistry of nitrones. In addition to the acyclic nitrone systems, in recent years, we have also proposed [10][11][12][13] the possible photo-isomerization mechanisms for most of the above-mentioned cyclic nitrone systems through quantum mechanical investigations. These studies have indicated that the nitrone to oxaziridine conversion process goes through a low-lying S 0 /S 1 conical intersection (CI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, our group has been actively involved in the investigations on the photochemistry of nitrones. In addition to the acyclic nitrone systems, in recent years, we have also proposed [10][11][12][13] the possible photo-isomerization mechanisms for most of the above-mentioned cyclic nitrone systems through quantum mechanical investigations. These studies have indicated that the nitrone to oxaziridine conversion process goes through a low-lying S 0 /S 1 conical intersection (CI).…”
Section: Introductionmentioning
confidence: 99%
“…It can be added here that in the last few decades, several photochemical reactions have been reported where the involvement of CIs have been found. In our earlier studies on the cyclic nitrone systems, [11][12][13] we have studied various pyrroline 1-oxide and 2H-imidazole-1,3-dioxide systems. There remains huge scope to explore the mechanism of the photochemistry of the substituted 2H-imidazole 1-oxide systems.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our group has proposed [ 10–13 ] the possible mechanism of photo‐isomerization for most of these above‐mentioned systems through high‐level computational studies. These investigations have revealed that the conversion of nitrone to oxaziridine goes through a low‐lying conical intersection (CI).…”
Section: Introductionmentioning
confidence: 99%
“…[7] Nature of this cyclic nitrone is quite different in comparison with 5,5-dimethyl-1-pyrroline 1-oxide (DMPO) [4] and its 2-methyl-substituted analogue (2-Me-DMPO). [5] In recent years, our group has proposed [10][11][12][13] the possible mechanism of photo-isomerization for most of these above-mentioned systems through high-level computational studies. These investigations have revealed that the conversion of nitrone to oxaziridine goes through a lowlying conical intersection (CI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation